Removal Of Copper From Water Using Columns Experiment Of Lignite, Shale, And Ironsand - Ty Boreborey; Wahyu Wilopo; Doni Prakasa Eka Putra (Journal of Applied Geology, 2015)
Experimental studies using column testing of lignite, shale, and ironsand in copper solution were carried out to determine the adsorption capacity of lignite, shale, and ironsand in remediation of water contaminated with copper. Lignite, shale, and ironsand were analyzed using XRD, SEM/EDX, and XRF. The treatment process by column adsorption was carried out over a period of 24 hours at a stable velocity of 0.005ml/s. After treatment, the remaining copper in the solution was recorded, thus allowing the adsorption capacity of lignite, shale, and ironsand to be calculated. The results revealed that when the solution was treated by lignite and shale there was a good degree of copper removal, while the ironsand had very poor degree of copper removal. The best material for copper removal was lignite with 25-mesh grain size. Pyrite, graphite, calcite, and illite were found in lignite and smectite, calcite, pyrite, hematite, and illite were found in shale. These materials were also shown to contain an abundance of high-valence elements in Al2O3, SiO2, and Fe3O4 which contributes to additional adsorption capacity. CAC values for lignite and shale reached nearly to 100%, suggesting that lignite and shale have a high adsorption capacity. In contrast, ironsand, which has mostly sand minerals with little clay and organic content, caused the pollutant to move rapidly to the water table, reducing the adsorption potential. CAC values treated by ironsand were shown to be negative which showed an increasing of Cu2+ in natural ironsand into solution. Keywords: Copper, ironsand, shale, lignite, column experiment